2022
DOI: 10.1016/j.heliyon.2022.e08746
|View full text |Cite
|
Sign up to set email alerts
|

Leaf growth, gas exchange and assimilation performance of cowpea varieties in response to Bradyrhizobium inoculation

Abstract: Supplying nitrogen to crops through selecting high N fixing legumes and effective inoculant is one of the key strategies to improve crop productivity. However, studies related to the effect of Bradyrhizobial inoculation on leaf growth, its functioning in relation to photosynthesis, and transpiration efficiency (WUE) of cowpea [ Vigna unguiculata (L.) Walp] varieties in the tropics were inadequate. A two-year field experiment was conducted at three sites to evaluate the effect of inoculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…(2014) also observed that stomatal conductance and transpiration rate followed a trend similar to the photosynthetic rate in cowpea submitted to different shading levels, and this result was attributed to a high correlation between these variables. With the increase in transpiration rate, stomatal conductance, and photosynthetic rate, there was an increase in CO 2 consumed and a reduction of internal carbon, similar to that observed in the literature (Ayalew et al., 2022; Cotrim et al., 2021). Under ideal conditions, there is an increase in the photosynthetic rate and consequent increase in CO 2 processing, which results in internal carbon reduction (Cotrim et al., 2021).…”
Section: Resultssupporting
confidence: 84%
“…(2014) also observed that stomatal conductance and transpiration rate followed a trend similar to the photosynthetic rate in cowpea submitted to different shading levels, and this result was attributed to a high correlation between these variables. With the increase in transpiration rate, stomatal conductance, and photosynthetic rate, there was an increase in CO 2 consumed and a reduction of internal carbon, similar to that observed in the literature (Ayalew et al., 2022; Cotrim et al., 2021). Under ideal conditions, there is an increase in the photosynthetic rate and consequent increase in CO 2 processing, which results in internal carbon reduction (Cotrim et al., 2021).…”
Section: Resultssupporting
confidence: 84%
“…Increases in vegetative growth are associated with increased nitrogen supply through biological nitrogen fixation (Ayalew et al, 2022). These effects may be related to the occurrence of heterogeneous nodulation through the increase of the root area, thus increasing the sites of infection (Fukami et al, 2018;Galindo et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…It was measured by using a portable leaf area meter (model LI-3000A Li-COR, Lincoln, USA). Then, leaf area indexes (LAI) were calculated by using the following equation [ 19 ]: …”
Section: Methodsmentioning
confidence: 99%